2014
DOI: 10.1016/j.dcn.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms of inhibitory control continue to mature in adolescence

Abstract: Inhibition is a fundamental executive function necessary for self-management of behaviour. The ability to withhold prepotent responses shows protracted development, extending through childhood and into adulthood. Using magnetoencephalography (MEG) with co-registered MRI, the spatiotemporal neural processes involved in inhibitory control were examined in 15 adolescents and 15 adults during a Go/No-go task. Two tasks were run that contained inverse ratios of Go to No-go trials for the experimental (2:1) and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
61
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 72 publications
4
61
1
3
Order By: Relevance
“…7,9,28 However, the current findings suggest that unremitting TS into late adolescence or adulthood may express a specific vulnerability in inhibitory control circuitries. 10,29,30 Imaging data has also linked persistent TS in early adulthood to structural and functional differences in prefrontal and basal ganglia circuitries that are implicated in inhibitory control.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…7,9,28 However, the current findings suggest that unremitting TS into late adolescence or adulthood may express a specific vulnerability in inhibitory control circuitries. 10,29,30 Imaging data has also linked persistent TS in early adulthood to structural and functional differences in prefrontal and basal ganglia circuitries that are implicated in inhibitory control.…”
Section: Discussioncontrasting
confidence: 42%
“…5,6 This has led to the conjecture that the persistent efforts to control tic behavior in childhood and early adolescence may actually contribute to the development of an overcompensatory inhibitory control system. 7,8 Moreover, many individuals with TS show remission or significant reduction of tic behavior in late adolescence and early adulthood around the same time that inhibitory control mechanisms fully mature, 9 although no studies have directly investigated longitudinal changes in inhibitory control in individuals whose symptoms remit. At first glance, these findings are not easily reconcilable with the idea that TS is accompanied by a generalized disruption to inhibitory control mechanisms.…”
mentioning
confidence: 99%
“…In line with the apparent similarities across common executive and inhibition related activation maps, our findings demonstrated areas of statistically significant shared activation across common executive and inhibition. Although, direct comparison between activation pertaining to inhibition and common executive has not been the focus, many previous studies have reported corresponding areas of activation for these constructs in child, adolescent and adult samples (Wager et al, 2005; Velanova et al, 2008; Niendam et al, 2012; Vara et al, 2014; Lei et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…The gradual neuroanatomical development is accompanied by functional changes promoting efficient and fast recruitment of the inhibitory networks well into young adulthood. Using MEG with co-registered MRI, Vara, Pang, Vidal, Anagnostou, and Taylor (2014) compared spatiotemporal neural processes during a Go/No-Go task between adolescents (aged 13–17 years) and adults (aged 20–35 years) and found indications of an immature inhibitory control network in adolescence. Adults showed right dominant inferior frontal activity, while adolescents showed left dominant, bilateral activity in the inferior frontal regions, but also delayed recruitment of the left inferior frontal gyrus, prolonged recruitment of the right middle temporal gyrus and additional recruitment of the superior temporal gyrus compared to adults.…”
Section: Introductionmentioning
confidence: 99%
“…The P3 deflection occurs between 300 and 500 ms and is greater during salient stimuli requiring response inhibition/execution (Randall & Smith, 2011; Smith, Jamadar, Provost, & Michie, 2013). Its generators are estimated to a wider network including lateral orbitofrontal and anterior cingulate cortices, inferior parietal lobe and pre-supplementary motor area (Albert et al, 2013; Vara et al, 2014). Studies investigating neural mechanisms underlying inhibitory control in children and adolescents showed age-related decreases in frontal N2 and increases in frontal P3 amplitude concurrent with improved behavioral performance (Jonkman, 2006; Lamm, Zelazo, & Lewis, 2006).…”
Section: Introductionmentioning
confidence: 99%